2017
DOI: 10.1016/j.ijscr.2017.03.043
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell tumor in grey zone: A case report

Abstract: HighlightsLeydig cell tumor is a testicular tumor with a low incidence accounting for 1–3% of testicular neoplasms.Only about 10% of them show malignant behavior in the form of metastatic disease.When diagnosed and treated early, long-term favorable outcomes are seen even with its potential metastatic behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…However, the strongest indicator of malignancy is the presence of metastases (8). Malignant tumors occur exclusively in adults and are unaccompanied by endocrine changes (1,9). In our case, the tumors size was 15 mm, the patient was young, there were no vascular invasion, cytological atypia or necrosis and surgical margins were negative and no distant metastasis was found.…”
Section: Discussionmentioning
confidence: 53%
“…However, the strongest indicator of malignancy is the presence of metastases (8). Malignant tumors occur exclusively in adults and are unaccompanied by endocrine changes (1,9). In our case, the tumors size was 15 mm, the patient was young, there were no vascular invasion, cytological atypia or necrosis and surgical margins were negative and no distant metastasis was found.…”
Section: Discussionmentioning
confidence: 53%
“…Clinically, LCT presents as a potentially malignant testicular mass with or without endocrine abnormalities such as loss of libido and gynecomastia. [ 1 ] There are 2 age peaks in the incidence of LCT: 30 to 60 years in adult and 3 to 9 years in child. [ 1 ] According to the review by Efthimiou et al, [ 11 ] 480 cases of LCT have been reported in the English literature and 29.2% of them are presented as testicular mass, 12.5% with gynecomastia.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] There are 2 age peaks in the incidence of LCT: 30 to 60 years in adult and 3 to 9 years in child. [ 1 ] According to the review by Efthimiou et al, [ 11 ] 480 cases of LCT have been reported in the English literature and 29.2% of them are presented as testicular mass, 12.5% with gynecomastia. The mechanism of hormonal disorders is likely to be excess production of testosterone and estrogens by the tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations